IMPROVING ENGLISH LEARNING MOTIVATION OF VISUAL COMMUNICATION DESIGN STUDENTS THROUGH JIGSAW METHOD AT STMIK ASIA MALANG - Tri Wahyuni (UMBanjarmasin, 2019)
This study aims to improve motivation through jigsaw method. This research was a classroom action research. The subjects were students of S1 degree from Visual Communication Design or Desain Komunikasi Visual (DKV) STMIK Asia Malang at 2018/2019 academic year. The action research was conducted to measure how jigsaw method can improve students’ learning motivation in the English subject. The data were collected using learning motivation questionnaire which were classified into good, enough, fair, and bad classification. Data were analyzed using descriptive analysis. This research shows that there is an improvement in students’ learning motivation through jigsaw method with an average score from the first cycle to the second cycle is 95%. The researcher suggests that teachers need to apply various learning activities through group discussion especially jigsaw. Jigsaw can improve students’ learning motivation as students can actively involve in the teaching learning process.